Scientific detectors for astronomy 2005 : explorers of the photon odyssey - Scientific Detector Workshop (6th : 2005 : Taormina, Italy); Beletic, Jenna E.; Beletic, James W.; Amico, Paola (Dordrecht : Springer, 2006)
26